Studi tentang Pelayanan dan Fasilitas asrama di Sekolah Tinggi Penerbangan Indonesia, Curug – Tangerang, September 2016. Tujuan dari Penelitian ini adalah untuk mengetahui permasalahan yang ada di Sekolah Tinggi Penerbangan Indonesia, Curug Tangerang terh - Made Arya; Ika Endrawijaya (Politeknik Penerbangan Indonesia Curug, 2017)
Made Arya, SE, M.Si, Ir. Ika Endra Wijaya, MMTr Research : The Study of dormitory services and facilities at Indonesian Aviation Training Institute Curug Tangerang , September 2016 The aim of this research is to know about the existing problems of student dormitory services and facilities at Indonesian Aviation Training Institute Curug Tangerang, in order to make them feel satisfied and comfortable in the dormitories. The research method is descriptive analyses and collecting data by documentation, observation, interview and book study